CALCULATION OF «VULNERABILITY» ZONE IN CASE OF TERRORIST ATTACK WITH CHEMICAL AGENTS - Biliaiev, M. M.; Berlov, O. V.; Kalashnikov, I. V.; Kozachyna, V. A. (Science and Transport Progress, 2018)
Purpose. The work involves the development of a numerical model for calculating the «vulnerability» zone of a possible terrorist attack objective with the use of a chemical agent in a built-up environment. The «vulnerability» zone is a territory near the attack objective, where the emission of a chemical agent during the attack will lead to undesirable consequences. The emission of a chemical agent outside the «vulnerability» zone will not create a dangerous concentration near the attack objective. Methodology. To solve this problem, we use the equation for the velocity potential, on the basis of which we determine the wind stream velocity field, and the equation adjoint to the equation of mass transfer in the atmospheric air of the chemical agent emitted in the event of a terrorist attack. During simulation, we take into account the uneven wind stream velocity field, atmospheric diffusion and the rate of emission of a chemically hazardous substance. For the numerical integration of the velocity potential equation, we use the method of A. A. Samarsky. For numerical solution of the adjoint equation, we introduce new variables and use an implicit difference splitting scheme. The peculiarity of the developed numerical model is the possibility of operative estimation of the «vulnerability» zone near a possible attack objective. Findings. The developed numerical model and computer program can be used for scientifically grounded assessment of the «vulnerability» zone near significant facilities in the event of possible attacks with the use of chemical (biological) agents. The constructed numerical model can be implemented on computers of small and medium power, which allows it to be widely used to solve the problems of this class when developing the emergency response plan. The results of the computational experiment are presented, which allow us to evaluate the possibilities of the proposed numerical model. Originality. An effective numerical model is proposed for calculating the «vulnerability» zone near the facility, which may be the target of a terrorist attack with the use of a chemical agent. The model is based on the numerical integration of the velocity potential equation and the equation adjoint to the equation of mass transfer of a chemically dangerous substance in the atmosphere. Practical value. The developed model can be used to organize protective actions near the target facility of a possible chemical attack by terrorists.